KAJIAN PEMILIHAN PEKERJAAN BASEMENT PADA BANGUNAN BERTINGKAT TINGGI MENGGUNAKAN METODE TOP DOWN SEBAGAI INOVASI METODE PELAKSANAAN (STUDI KASUS : PROYEK SUDIRMAN SUITES HOTEL AND APARTMENT JAKARTA) - Nopirin Abliataniaga Bintang; Mahayekti Bagaskara; M. Agung Wibowo; Arif Hidayat (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
This paper explains on studies of top down basement construction method on high rise building as innovation of construction method. Nowadays, in the world of construction there are varies of innovations; one of them is top down method for basement construction. Sudirman Suites Hotel and Apartment is a project of 22 levels building and 5 levels of basement located in the middle of large city where there are already many buildings and activities surrounding. PT. Wika Gedung as a main contractor decided to apply top down method for 5 levels of basement with 24,4 m deep. As comparation there is Menara Sentraya project on Blok-M, which conventionally constructed with bottom up method. This research uses Sudirman Suites Hotel and Apartment’s site manager’s correspondency as primary data. Shop drawings, proposed budget, time schedule and site plan for the secondary data. Data analyzation method is to compare primary data on both project and uses secondary data for validation. Main reason for top down method for basement construction is the limited project area, only 4792.331 m2 and 2769.15 m2 for the excavation zone, moreover, open cut is not feasible to excavate 24,4 m deep without any reinforcements.